Peranan Eco-Enzyme terhadap Perubahan Hara N Tanah dan Pertumbuhan Awal Padi pada Tanah Sawah Tadah Hujan - Sakti Agrianto Suwandi; Fakhrur Razie; Afiah Hayati (Acta Solum, 2024)
Acid mineral soils in Indonesia mostly develop in wet tropical climates supported by high temperatures, so the weathering process runs faster than in dry climate areas. High rainfall causes intensive leaching, so basic cations are lost from the soil layer, and the soil has low base saturation. Some acid mineral soils in Indonesia are farmed under rainfed systems. This soil has a low nutrient availability status compared to irrigated rice fields, due to the lack of water availability, and is still dependent on rainfall. Eco-Enzyme (EE) contains several nutrients and microbes from fermentation that can increase soil fertility. This research aims to determine the effect of EE N nutrient availability and early rice growth in rainfed paddy fields. This study uses a Completely Randomized Design single factor, namely the total bacterial population in EE consisting of 5 treatments, namely K0= control; K1= 8,1 x 106 cells mL-1 in EE; K2= 1,2 x 107 cells mL-1 in EE; K3= 1,6 x 107 cells mL-1 in EE; and K4= 2 x 107 cells mL-1 in EE. Each treatment was repeated 4 times so that there were 20 experimental units. The results of the study show that the provision of the total bacterial population in EE 1,2 x 107 cells mL-1 can increase the pH to 5,38, N-NH4+ to 154,60 mg kg-1, and N-NO3- to 8,26 mg kg-1. Giving total bacteria in EE 1,6 x 107 cells mL-1 can increase the viability of non-symbiotic N2 fixing microbes.